Transitional Justice in Southeast Asia: Theory and Practice - Aulia Nastiti (Asia-Pacific Journal of Elections and Democracy, 2021)
The issue of transitional justice has largely evaded the theoretical discussion on the democratization in Southeast Asian context despite the importance of coming to terms with the history of abuse and violence of the past authoritarian regimes. This article fills out this lacuna by incorporating the regional analysis of transitional justice process in several Southeast Asian countries to the larger and mainstream theories of transitional justices that are developed from other contexts. Using the case of transitional justice in Cambodia, East Timor, the Philippines, and Indonesia, this article found that the two most predominant accounts in the literature – the “balance of power” and the “justice cascade” theories – are inadequate to explain the conditions of emergence of the transitional justice and the kind of justice measure that the state would adopt. In turn, studies of empirical cases in these four Southeast Asian countries shed light on three plausible factors previously overlooked in the literatures: a) the distinctive, locally based, notion of justice; b) the frame and narrative of legitimacy of past violence; and c) the degree of complicity and entrenchment of current ruling elites in the past conflict.